Carbide cutting blade

By controlling the KAM value and using a specific carbide alloy composition, the carbide cutting blade addresses issues of low durability and chipping, resulting in improved cutting accuracy and longevity.

JP7670850B2Active Publication Date: 2025-04-30A L M T CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023559064
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-18
Filing Date
2023-03-14
Publication Date
2025-04-30
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

Conventional carbide cutting blades suffer from low durability and are prone to chipping, which affects the cutting surface quality and resistance.

Method used

A carbide cutting blade with a controlled KAM value (between 0 and 4.0) for the WC particles constituting the blade surfaces, combined with a specific composition of tungsten carbide and cobalt, and a two-stage blade design to reduce strain and enhance defect resistance.

Benefits of technology

The solution significantly reduces chip formation and size, suppresses cracks and chipping, and enhances the cutting blade's longevity and accuracy, even at sharp edge angles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670850000009
    Figure 0007670850000009
  • Figure 0007670850000010
    Figure 0007670850000010
  • Figure 0007670850000011
    Figure 0007670850000011
Patent Text Reader

Abstract

This cutting blade made of a super-hard alloy comprises a base portion, and a blade portion provided on an extension line of the base portion and having a blade tip, which is a tip end portion. A KAM value, which represents distortion of WC particles constituting left and right blade surfaces forming the blade tip, is 0 to 4.0 inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a cutting blade made of cemented carbide. This application claims priority to Japanese Patent Application No. 2022-043430, filed on March 18, 2022. All contents of the Japanese Patent Application are incorporated herein by reference. [Background technology]

[0002] Conventionally, cutting blades made of cemented carbide have been disclosed, for example, in JP 10-217181 A (Patent Document 1), WO 2014-050884 A (Patent Document 2), and JP 2004-17444 A (Patent Document 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-217181 [Patent Document 2] International Publication No. 2014-050884 [Patent Document 3] JP 2004-17444 A Summary of the Invention

[0004] The cemented carbide cutting blade has a base and a blade portion that is located on an extension of the base and has a cutting edge at the most distal end, and the KAM value, which is the distortion of the WC particles that make up the left and right blade surfaces that form the cutting edge, is between 0 and 4.0. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a front view of a cutting blade 1 made of cemented carbide. [Diagram 2] FIG. 2 is a perspective view of the cemented carbide cutting blade 1. As shown in FIG. [Diagram 3] FIG. 3 is a perspective view of a two-stage cutting blade 1 made of cemented carbide. [Figure 4]FIG. 4 is a front view of the cemented carbide cutting blade 1 shown for explaining the cutting method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] [Problem that this disclosure aims to solve] Conventional cutting blades made of cemented carbide have a problem of low durability.

[0007] Patent Document 1 (JP Patent Publication No. 10-217181) discloses a flat cutting blade for cutting thin plate-like workpieces such as ceramic green sheets, which has high buckling strength while maintaining a narrow cutting edge angle that enables high-precision cutting.

[0008] As a solution to this problem, it is proposed to form the cutting edge portion as a plane or a concave curved surface that is symmetrical with respect to the center line Y, and to connect the cutting edge portion and the base portion with a reinforcing section that is a one- or multiple-stage symmetrical concave curved surface, thereby shortening the distance of the cutting portion and increasing the buckling strength while ensuring high-precision cutting processing.

[0009] Patent Document 2 (International Publication No. 2014-050884) describes a cutting edge having a flat base, left and right blade surfaces inclined from both sides of the base so as to approach each other, and a cutting edge tip having a convex curved surface formed to connect the left and right blade surfaces. In the cross-sectional shape in the plate thickness direction, the intersection of two straight lines along the left and right blade surfaces and the Most The present invention proposes a flat cutting blade characterized in that the short distance is 1 μm or more and 10 μm or less, the length of the tip portion differs between the left and right sides of the center line of the base portion, the difference being 1 μm or more and 20 μm or less, and further the interior angle of the intersection angle between two straight lines along the left and right blade surfaces is 4 degrees or more and 60 degrees or less.

[0010] Patent Document 3 (JP Patent Publication 2004-17444A) discloses that a grinding groove can be easily formed by using a cup-shaped grindstone. It discloses a cutting blade having a substantially rectangular shape that cuts a plate-shaped ceramic body by applying a pressing force in the thickness direction of the body, the cutting blade having a blade surface formed by a flat surface along one side in the long side direction, a grinding groove extending in the short side direction formed on the blade surface, the blade surface being composed of a plurality of stepped surfaces divided in the short side direction, and the stepped surface closer to the cutting edge has a larger angle.

[0011] In recent years, the high density lamination technology of MLCC (Multilayer Ceramic Capacitors) has led to the downsizing of large MLCCs. The downsizing has led to an increase in the number of layers of Ni electrodes, and the distance between electrodes in the thickness direction has been reduced to hundreds of nm or less by reducing the particle size of the dielectric barium titanate to several tens of nm. As a result, the hardness of the green sheet has increased, and the cut surface quality tends to deteriorate as the distance between the electrodes becomes shorter. In this situation, this patent relates to an invention that provides a long-life cemented carbide cutter by suppressing the distortion (processing damage) of the WC particles that make up the cutting edge, increasing chipping resistance, and suppressing the deterioration of the cut surface quality and cutting resistance due to chipping.

[0012] To manufacture multilayer ceramic capacitors, there is a need to cut laminated green sheets with thicknesses ranging from several hundred microns to several millimeters. After cutting these continuously with high precision, each cut piece is fired and electrodes are attached to both ends to make a capacitor. In recent years, there has been an increasing demand for smaller capacitors to fit small devices such as smartphones, and this requires high cutting precision. To realize such small-sized ceramic capacitors, it is necessary to prevent damage to the cut surface of the green sheets by reducing the distortion of WC particles that occurs during cutting of the cutting edge and by suppressing chipping that develops from the impact and thermal displacement that occurs when using a cutter.

[0013] There are two methods for cutting the green sheet: a method using a rotating circular blade called a dicing method, and a push-cut method using a flat cutting blade as disclosed in the present invention. The former has the disadvantages of poor material yield due to the large amount of cutting waste and slow cutting speed, but the push-cut method is useful for small-sized products.

[0014] Fig. 1 is a front view of a cemented carbide cutting blade 1. Fig. 2 is a perspective view of the cemented carbide cutting blade 1. Fig. 3 is a perspective view of a two-stage cemented carbide cutting blade 1.

[0015] As shown in Figures 1 to 3, the cemented carbide cutting blade 1 has a cutting edge portion 2 that performs cutting, a connecting portion 3 that is connected to the cutting edge portion 2, and a base portion 4 that is connected to the connecting portion 3 and fixed by a cutting blade fixing portion 5.

[0016] The cutting edge 2 is pressed against the workpiece 100, thereby cutting the workpiece 100. The cemented carbide cutting blade 1, which serves as a flat cutting blade, extends in the x direction perpendicular to the y and z directions in FIG.

[0017] Blade surfaces 201 and 202 are provided on both sides of the blade tip 2. In Fig. 3, blade surfaces 203 and 204 are provided to form a two-stage blade. Each of the blade surfaces 201 to 204 may be linear or curved. The ridge where the blade surface 201 and the blade surface 202 intersect is the blade tip 210.

[0018] The cemented carbide cutting blade 1 according to the present disclosure comprises a connecting portion 3 as a base, and a cutting edge portion 2 as a blade portion that is provided on an extension line of the connecting portion 3 and has a cutting edge 210 as the most distal end, and the KAM value, which is the distortion of the WC particles that constitute the left and right blade surfaces 201, 202 that form the cutting edge 210, is between 0 and 4.0.

[0019] In the cemented carbide cutting blade 1 configured in this manner, the KAM value, which is the distortion of the WC particles that make up the blade surfaces 201, 202, is from 0 to 4.0, so that cracks inside the WC can be suppressed and chipping resistance can be increased.

[0020] Preferably, the KAM value is 0.3 or more and 4.0 or less, and more preferably, the KAM value is 0.3 or more and 2.1 or less.

[0021] Preferably, the content of cobalt in the cemented carbide is greater than or equal to 3 mass % and less than or equal to 25 mass %. Preferably, the cemented carbide has a Vickers hardness of Hv1300 or more and 2030 or less.

[0022] Such thin blades are made of hard materials such as carbon tool steel, stainless steel, and cemented carbide. However, they are not easy to process, and the reasons for this include that, especially when the material is a hard material, although it has rigidity, it is difficult to cut and has low toughness, making it prone to chipping, and when the blade is thin, even if it is made of a hard material, the blade tends to break away due to the pressure of the grindstone during processing, especially at the tip of the blade. Furthermore, deterioration of the WC that constitutes the blade surface can be caused by external disturbances such as the precision of the processing machine, changes in the grindstone over time, and vibration.

[0023] Conventionally, various cutting blades have been proposed to satisfy the above-mentioned characteristics, but when the shape is made complex, it is inevitable that processing becomes even more difficult, and a cutting blade that satisfies both stable shape accuracy and processability has not been obtained.

[0024] effect The number of chips that occur and the size of the chips can be reduced.

[0025] The strain value of the WC grains was obtained by using the SEM / EBSD (Electron Back Scatter Diffraction) method to obtain the crystal orientation distribution (orientation map) of the entire measurement area, and the internal residual strain was quantified by measuring the KAM (kernel average misorientation) value map from the crystal orientation difference information. As a result, it was found that by keeping the KAM value below 4.0, it is possible to suppress cracks inside the WC and improve chipping resistance. By using this method, it is possible to suppress chipping even with an acute cutting edge angle θ without making the cutting edge obtuse, and it is possible to provide a carbide cutting blade with long-lasting sharpness and long life.

[0026] Material The material used for the cutting blade is a cemented carbide alloy mainly composed of tungsten carbide and cobalt, and the size of the tungsten carbide crystal grains in the alloy has an average grain size of 0.1 μm to 4 μm, preferably 2 μm or less. The average grain size was determined by measuring the surface of the cemented carbide alloy in an SEM photograph at a magnification of 10,000 times, randomly selecting 100 crystals, calculating the grain size of each crystal based on the formula (major axis + minor axis) / 2, and averaging the grain sizes of the 100 crystals.

[0027] Also, in order to control the crystal grains of tungsten carbide, it is possible to add 0.1 to 2 mass% of TaC (tantalum carbide) as a component for suppressing crystal grain growth. This additive can be replaced with or combined with V8C7 (vanadium carbide) and Cr3C2 (chromium carbide). In that case, the amount of each additive is 0.1 to 2 mass%. The amount of cobalt used in the cemented carbide is preferably in the range of 3 to 25 mass%, more preferably in the range of 5 to 20 mass%. TaC, V8C7, and Cr3C2 are dissolved from the cemented carbide using nitric acid and hydrofluoric acid, and then the liquid is subjected to an ICP emission spectroscopic analysis (EIA). light The mass of Co can be measured by spectroscopic analysis. Co can be dissolved from the cemented carbide using nitric acid and hydrofluoric acid, and the mass of the solution with the adjusted pH can be measured using a potentiometric titration apparatus (potentiometric titration method).

[0028] The hardness of the cemented carbide is preferably in the range of 1,300 to 2,030 in Vickers hardness Hv, and more preferably in the range of 1,850 to 2,150.

[0029] Thickness The base thickness T of the cemented carbide cutting blade is preferably 0.1 mm or more to 0.6 mm or less. By making it within this range, it can be used as a cutting blade (compatible with a cutting machine) for laminated ceramic green sheets. A cutter with a thickness of 0.1 mm can reduce the grinding allowance when grinding to produce an acute-angled blade with a cutting edge angle of 20° or the like for thin chips of ceramic capacitors, and can reduce the grinding resistance, making it possible to create a highly accurate cutting edge. On the other hand, a cutter with a base thickness of 0.4 to 0.6 mm is suitable for cutting thick chips with a thickness of 1 mm or more because the rigidity (flexure at the base of the cutting edge) can be improved by increasing the thickness of the cutter itself. In addition, there is an advantage that the rigidity of the base of the blade is increased, making it less likely to cause oblique cutting.

[0030] The thickness of the carbide cutting blade can be measured using a micrometer or a laser measuring device. The relationship between the length L (mm) and the height W (mm) of the cemented carbide cutting blade (FIG. 2) is preferably 1≦L / W≦20.

[0031] The cutting edge angle θ is preferably in the range of 6°≦θ≦30°. The smaller the cutting edge angle, the smaller the cutting resistance and the less likely diagonal cuts will occur. In other words, the volume that penetrates the workpiece is smaller. For angles of 10° or less, a single-stage blade is sufficient, but since the width dimension that forms the cutting edge becomes larger, there are problems such as the cutting edge being prone to tipping due to grinding resistance and it being difficult to machine the cutting edge into a highly accurate shape. It is known that chipping during sharpening becomes extremely likely to occur when the boundary is θ≦20°.

[0032] Working Example The cutting edge was formed using a cemented carbide FM10K material manufactured by A.L.M.T. Co., Ltd. The flat blade used in the test had a cutting edge direction L of 40 mm, a base thickness T of 0.1 mm, and a blade height W of 25.0 mm. The cutting edge angle θ of the cutting edge 2 as the cutting execution part was 20°±5', the first stage blade width was 0.1 mm, and the second stage blade angle (the angle formed by the intersection of the extended surface of the second stage blade face) was 4°±10'. In the cutting edge forming process, a surface grinder was used, a diamond cylindrical grinding wheel was used to true the side of the grinding wheel, and the material was fixed to a dedicated work rest with an adjustable angle and processed. As a result, cemented carbide cutting blades 1 of sample numbers 1 to 45, 101 to 145, 201 to 245, and 301 to 345 shown in Tables 1 to 8 were produced.

[0033] [Table 1]

[0034] [Table 2]

[0035] [Table 3]

[0036] [Table 4]

[0037] [Table 5]

[0038] [Table 6]

[0039] [Table 7]

[0040]

Table 8

[0041] <Removal of residual strain on WC surface of cutting edge> By performing electrochemical polishing using electrolytic polishing, the surface of the cutting edge of the cemented carbide was removed, and the strain that was presumably left during the formation of the cutting edge by the grinding wheel remaining on the cutting surface forming the tip angle was removed. The cutting edge of the cutting blade was directed downward, and an electrode formed in a shape conforming to its shape was placed at the bottom. These were immersed in an electrolyte containing 100 g / dm 3 of NaNO3, and a power supply was arranged so that the cemented carbide cutting blade became the anode, and the voltage was adjusted to a current density of about 0.1 to 1.0 A / cm 2 .

[0042] During electrolytic polishing, the polishing conditions and polishing time were adjusted while checking the surface state of the cemented carbide cutting blade. <Measurement of surface roughness> For the measurement of the surface roughness Sa (arithmetic mean roughness) of the cutting surface, a non-contact three-dimensional roughness measuring device (Nexview (registered trademark)) manufactured by Zygo Corporation was used, and the measurement range in the above longitudinal section was set to 140 μm in the X direction directly below the cutting edge and 30 μm in the Z direction. The measurement field of view was set to a magnification of 50 times for the objective lens and a ZOOM magnification of ×1 time.

[0043] <Measurement of cutting edge ridge width> For the measurement of the ridge width of the cutting edge, an image was taken from a direction orthogonal to the cutting edge ridge at a magnification of 5,000 to 10,000 times using a Schottky field emission type scanning electron microscope JSM7900F manufactured by JEOL Ltd., and the measurement was performed using the machine coordinates and the length measurement function. In all samples, it was confirmed that the cutting edge ridge width was 0.5 μm or less, and these were used for the test blades.

[0044] <Measurement of WC strain> The distortion of the WC grains on the left and right blade surfaces 201, 202 that make up the cutting edge 210 is measured by using a reflection electron beam diffraction pattern (channeling pattern) formed by using the electron backscatter diffraction (SEM) method (Electron Back Scatter Diffraction) mounted on the aforementioned electron microscope to measure the crystal orientation. The measurement conditions were a measurement magnification of 20,000 times, an acceleration voltage of 25 KV, and an irradiation current of 12 nA, and the cutting edge was tilted 70° and an electron beam was applied to the reflection electron beam diffraction pattern (channeling pattern) formed, and the distortion of the cutting edge surface was quantified and evaluated by measuring the KAM (kernel average misorientation value) map.

[0045] <Crack measurement> The chipping of the cutting blade was measured using an Olympus STM-UM tool measuring microscope at 500x magnification. It was confirmed that the chipping depth was within 1.5 μm and the chipping width was within 10 μm in all samples.

[0046] <Disconnection test> In order to confirm the effect of the cutting blade of the present invention, a polyvinyl chloride plate was cut by pushing and cutting, and the cut surface was evaluated based on the cutting resistance and the cutting marks made by the cutting blade on the workpiece. The effect of the present disclosure was confirmed. As shown in FIG. 4, the workpiece (work) 100 is cut with a cemented carbide cutting blade 1. An acrylic base 102 is placed on a cutting dynamometer 103. A thermal peeling adhesive sheet 101 is interposed between the base and the workpiece 100. The workpiece 100 is cut by moving the cemented carbide cutting blade 1 back and forth in the direction indicated by the arrow 111 while moving the workpiece 100 in the direction indicated by the arrow 110.

[0047] Conditions of this test Cutter specifications: cutting edge angle θ16°~20°, second stage angle 4°, thickness T: 0.1mm, length L: 40mm Workpiece material: PVC plate, thickness 0.5 mm, length 290 mm, width 30 mm Test equipment: Makino Milling Machine Co., Ltd. Machining Center V55 (hereinafter referred to as the cutting machine) with Kistler's cutting dynamometer 103 (hereinafter referred to as the cutting dynamometer). The workpiece set was placed on the dynamometer table. Thickness 10mm acrylic plate, 1mm thick foam double-sided adhesive sheet, thickness 0.5mm±0.1 mm The workpiece (the PVC board) (which constitutes the cut object 100) was used, and the cutter was attached with a blade angle of ±0.5° in the longitudinal direction of the workpiece and a blade cross-sectional angle of 90°±0.5° in the workpiece. The cutting conditions were a cutting speed of 300 mm / s, a cutting interval of 12 mm, and a pushing amount of 0.1 mm so that the blade tip cuts into the adhesive layer of the thermal release sheet. The PVC was cut 1000 times, and the cutting resistance, cut surface quality, and the number of chips of 10 μm or more were evaluated when cut once, 500 times, and 1000 times. The results of repeating this test under each condition are shown in Tables 1 to 8.

[0048] In Tables 1 to 8, the "Cut Surface" column was evaluated by observing the cut point at the 1000th cut (the final cut point) under a microscope. If there were three or fewer cut lines, the result was an "A," and if there were four or more cut lines, the result was a "B."

[0049] Regarding the KAM value, which is an index of distortion, good cutting results were obtained with no more than three cutting streaks due to chipping when the KAM value was between 0 and 4.0. The preferred KAM value range is between 0.3 and 4.0. The better range is between 0.3 and 2.1. below It is most preferable that the KAM value is 0.3 or less. However, since it is costly to set the KAM value in the range of 0 or more and less than 0.3, the KAM value is set to 0.3 or more in the above embodiment. In other words, from the viewpoint of performance alone, it is preferable that the KAM value is less than 0.3.

[0050] The "Chipped width" column in Tables 1 to 8 shows the number of chips with the corresponding chip width. The "10μm+" column shows the number of chips with widths exceeding 9.5μm, the "6μm-9μm" column shows the number of chips with widths exceeding 6.5μm and up to 9.5μm, and the "3μm-5μm" column shows the number of chips with widths exceeding 2.5μm and up to 5.5μm.

[0051] For the KAM value, good cutting results were obtained in terms of the number of chips when the KAM value was in the range of 0.3 to 4.0. The better range is when the KAM value is in the range of 0.3 to 2.1.

[0052] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0053] 1 Cemented carbide cutting blade, 2 cutting edge, 3 connecting part, 4 base, 5 cutting blade fixing part, 100 object to be cut, 201,202,203,204 blade surface, 210 cutting edge.

Claims

1. A cemented carbide cutting blade comprising a base and a blade portion provided on an extension of the base and having a cutting edge which is the most distal end, wherein a KAM value which is the distortion of WC particles constituting the left and right blade faces forming the cutting edge is between 0 and 4.0, and a ridge width of the cutting edge is 0.5 μm or less, the cemented carbide having a Vickers hardness of Hv 1300 or more and 2030 or less, and the cemented carbide cutting blade being made of a uniform composition.

2. 2. The cemented carbide cutting blade according to claim 1, wherein the KAM value is 0.3 or more and 4.0 or less.

3. The cemented carbide cutting blade according to claim 2, wherein the KAM value is 0.3 or more and 2.1 or less.

4. The cemented carbide cutting blade according to any one of claims 1 to 3, wherein the content of cobalt in the cemented carbide is in the range of 3 mass% to 25 mass%.

Citation Information

Patent Citations

  • Cutting blade and its molding method

    JP1998217181A

  • Cutting blade and blade face processing method therefor

    JP2004017444A

  • Cemented carbide and surface-coated cutting tool prepared using the same

    JP2015101747A

  • Coated cutting tool

    JP2019195872A

  • Coated cutting tool

    JP2021160017A